THE MOST TUNING RADIO FREQUENCIES AMONG TAMIL UNIVERSITY STUDENTS COMMUNITY: A USERS AND GRATIFICATION STUDY ON THE RADIO AUDIENCE - Sivapriya Sriram, K.G.L.A.N.S.Jayawardhana & J.Jairus (International Journal of Research Science and Management, 2020)
This exploratory study begins by attaining general knowledge about a group of students pertaining to their listening habits while applying uses and gratifications theory and then attempts to gauge whether or not the station meets student preferences. Of the 100 total participants, study in Trincomalee campus thus becoming the target audience for this study. To achieve objectives of this study, survey method has been used for data collection. A questionnaire was distributed among 100 respondents. Findings revealed that majority (90%) of the respondents listen to radio programmes and they prefer to listen to radio at any convenient time (33%), the respondents do listen radio channels mostly through mobile phones (65%), majority of the respondents do listen private radio channels (92.5%), the respondents mostly listen to Shakthi FM (46%), and respondents mostly listen to musical programmes (47%).